International law and transnational organized crime - Hauck, Pierre; Peterke, Sven (Oxford University Press, 2016)
The historical evolution of the international cooperation against transnational organised crime : an overview / Frank G. Madsen -- Transnational organised crime : concepts and critics / Arndt Sinn -- Transnational organised crime and its impacts on states and societies / Thomas Feltes and Robin Hofmann -- The EU and the fight against organised crime / Bernd Hecker -- Transnational organised crime and terrorism / Bettina Weiber -- The convention against illicit traffic in narcotic drugs and psychotropic substances 1988 and the global war on drugs / Richard Vogler and Shahrzad Fouladvand -- The UN convention against transnational organised crime 2000 / Neil Boister -- The UN protocol to prevent, suppress, and punish trafficking in persons 2000 / Hans-Joachim Heintze and Charlotte Lülf -- The UN protoco against the smuggling of migrants by land, sea and air 2000 / Andreas Schloenhardt -- The UN protocol against the illicit manufacturing and trafficking in firearms, their parts and components, and ammunition 2001 / Aaron X. Fellmeth -- The United Nations convention against corruption and its criminal law provisions / Michael Kubiciel and Anna Cornelia Rink -- Transnational organised crime and the anti-money laundering regime / Louis de Koker and Mark Turkington -- Transnational organised crime and the illegal trade in endangered species of wild fauna and flora / Hennie Strydom -- Transnational organised crime and the sale of children, child prostitution, and pornography / Thorsten Müller -- Transnational organised crime and cultural property / Bernhard Kretschmer -- Transnational organised crime and cybercrime / Dominik Brodowski -- The international law of the use of force and transnational organised crime / Pierre Thielbor̈ger -- International humanitarian law and transnational organised crime / Sven Peterke and Joachim Wolf -- Transnationnal criminal organisations and human rights / Math Noortmann and Dawn Sedman -- Law of the sea ant transnational organised crime / Alexander Proelss and Tobias Hofmann -- Transnational organised crime and international criminal law / Pierre Hauck -- Policing TOC : the national perspective : challenges, strategies, tactics / Sheelagh Brady -- Policing transnational organised crime : the international perspective / Frank G. Madsen